Mesozoic reactivation of the Beishan, southern Central Asian Orogenic Belt: Insights from low-temperature thermochronology - Gillespie, J.; Glorie, S.; Xiao, W.; Zhang, Z.; Collins, A.; Evans, Noreen; McInnes, Brent; Grave, J. (Elsevier, 2015)
The Beishan Orogenic Collage (BOC) is located in the southeast of the Central Asian Orogenic Belt (CAOB) and formed during final consumption of the Palaeoasian Ocean in the late Palaeozoic. This study applies low temperature thermochronology to constrain the Meso-Cenozoic history of the BOC. Apatite fission track and U–Th–Sm/He data obtained for granitoid samples along a north–south transect through the BOC indicate three distinct phases of exhumation during (1) the late Triassic–early Jurassic (~ 225–180 Ma), (2) early Cretaceous (~ 130–95 Ma) and (3) late Cretaceous–early Palaeogene (~ 75–60 Ma). Samples from the northern BOC reveal a more profound early Cretaceous signal and a weaker late Triassic–early Jurassic signal than those in the southern BOC. A possible explanation for this discrepancy is the presence of crustal-scale fault zones in the northern BOC that are interpreted to have undergone repeated reactivation throughout the Mesozoic, exposing deeper exhumed sections of the BOC. These faults may thus have acted as a major control on exhumation in the region. This pattern is consistent with results from elsewhere in the CAOB, such as in the Tianshan and the Altai, where regional widespread exhumation occurred since the early Cretaceous while major fault zones record localised exhumation during the late Cretaceous and Cenozoic. Late Cretaceous–early Palaeogene cooling ages were found only in the south of the BOC, suggesting that exhumation at that time was more localised and did not reach the northern margins of the study area.The Meso-Cenozoic cooling events described here are thought to be related to the progressive closure of the (Palaeo-)Tethys ocean to the south. Associated collision and accretion of micro-continental blocks and island–arcs at the southern Eurasian margin are interpreted to have induced more widespread reactivation and exhumation in Central Asia than previously anticipated, extending to the northern margin of the Tarim Craton. This observation hence refines the existing tectonic history models for Central Asia.